Communication barriers between gen Z and alpha in the cultural digitalization era - Wibisono, Bambang; Yusnita, Titis Rizka; Haryono, Akhmad (UNIB Press, 2025)
The role of culture in the interaction process also determines the effectiveness of communication that takes place between generations. This research aims to describe communication barriers that impact the effectiveness of interactions between Gen Z and Alpha in the era of cultural digitalization. The literature used is Chaney and Martin's theory of communication barriers which was processed through a process of observation and interviews. The research results showed that there were nine types of barriers found, namely physical, cultural, perceptual, motivational, experiantial, emotional, linguistic, non-verbal, and competition. The nine types of communication barriers are supported by explanations from sources or participants in the data. These findings show that there is a gap between Gen Z and Alpha, in this case in the context of cross-cultural communication. This has an impact on the emergence of quite complex communication barriers. Of the nine types of barriers, the barriers most frequently encountered are linguistic, motivational, and competition. Based on these findings, motivational communication barriers have the potential to give rise to conflict between Gen Z and Alpha due to a feeling of not being appreciated when interacting. The role of digital in this era also has an impact on hampering effectiveness of communication. Nevertheless, communication barriers from a cultural aspect need to be seen as the complexity of cultural diversity that exists in Indonesia, both language differences and other differences. This should not be claimed as a reason for conflict, but rather as a medium for tolerance and mutual respect so that communication barriers can be minimized. So, the communication process that occurs in the future can be more effective and harmonious.